The value of 2019 EULAR/ACR classification criteria in predicting lupus nephritis in childhood-onset systemic lupus erythematosus - Cetin, Nuran; Acikalin, Mustafa Fuat; Tufan, Asli Kavaz; Kasifoglu, Nilgun (Klinische Pädiatrie, 2023)
Background We investigated the role of European League Against Rheumatism (EULAR)/American College of Rheumatology (ACR) classification criteria for the prediction of LN among children with SLE.Methods The data of the patients with childhood-onset SLE diagnosed based on 2012 Systemic Lupus International Collaborating Clinics (SLICC) criteria were retrospectively evaluated. Based on 2019 EULAR/ACR classification criteria, the scoring was done at the time of renal biopsy.Results Fifty-two patients (12 with LN, 40 without LN) were included. The mean score was higher in patients with LN than those without (30.8±6.14, 19.8±7.76, respectively, p=0.000). The score value had indicative value for LN (area under curve [AUC]:0.863±0.055, cut-off value:22.5, p=0.000). Lymphocyte counts had a predictive value for LN (cut-off value:905/mm3, AUC:0.688±0.087, p=0.042). The score was positively associated with SLE disease activity index (SLEDAI) and activity index (r=0.879, p=0.000; r=0.811, p=0.001, respectively). There were significant negative associations between score value and GFR (r=-0.582, p=0.047). The patients with renal flare had higher the mean score than those of without renal flare (35±2/25.4±5.57, respectively, p=0.019).Conclusions The EULAR/ACR criteria score could reflect the activity of disease and severity of nephritis in childhood-onset SLE. A point of 22.5 as score value might be an indicator for LN. During scoring, it should be taken into account that lymphopenia might guide the prediction of LN.
Keywords: Lupus nephritis; 2019 EULAR/ACR classification criteria; children; systemic lupus erythematosus